(untitled) (Вісник: Міжнародні відносини, 2025)
Background. The impact of the Russian-Ukrainian war on global logistics networks and international economic relations is comprehensively analysed. The study focuses on the key economic consequences of the conflict, including disruptions in supply chains, changes in logistics routes, and the impact on energy markets, which has resulted in the need to diversify energy sources for Europe. Particular attention is paid to the international response to the conflict, including the imposition of sanctions against Russia and large-scale financial and military assistance to Ukraine. Methods. The study used a comprehensive approach that includes an analysis of scientific literature, a review of international economic reports, and a comparative analysis of the impact of previous geopolitical conflicts on the global economy. The use of quantitative and qualitative analysis methods allowed us to identify patterns and features of the impact of military operations on global economic processes. Results. The Russian-Ukrainian war has led to serious disruptions in global logistics networks, in particular due to the interruption of supply chains for critical goods and significant changes in the routes of transportation of products. The war has also caused significant disruptions in energy markets, which has resulted in a reduction in energy supplies from Russia and the need for Europe to urgently seek alternative energy sources. The sanctions imposed on Russia have had a significant negative impact on its economy, leading to its isolation on international markets. In response, the international community has mobilised significant resources to support Ukraine, which has become a key factor in maintaining its economic stability and military potential in the context of the conflict. Conclusions. The Russian-Ukrainian war has become a catalyst for significant changes in international economic relations and global logistics networks. It has exposed weaknesses in the global economic system, forcing many countries to rethink their approaches to economic cooperation and security. The long-term consequences of the war may include further strengthening of regional economic blocs, the formation of new trade alliances and supply chains, and the development of more resilient and flexible economic systems at the global level.